2019
DOI: 10.1111/brv.12514
|View full text |Cite
|
Sign up to set email alerts
|

A general framework for propagule dispersal in mangroves

Abstract: Dispersal allows species to shift their distributions in response to changing climate conditions. As a result, dispersal is considered a key process contributing to a species' long-term persistence. For many passive dispersers, fluid dynamics of wind and water fuel these movements and different species have developed remarkable adaptations for utilizing this energy to reach and colonize suitable habitats. The seafaring propagules (fruits and seeds) of mangroves represent an excellent example of such passive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 263 publications
(378 reference statements)
3
117
0
Order By: Relevance
“…In response to warming winter temperature extremes (USGCRP, ), mangroves and other tropical organisms are expected to move northward into more temperate biomes in eastern and central North America (Carter et al, ; Cavanaugh et al, ; Osland et al, ; Osland & Feher, ). In combination with temperature projections and models of mangrove propagule dispersal (Van der Stocken, Carroll, Menemenlis, Simard, & Koedam, ; Van der Stocken, Wee, et al, ), establishment (Krauss et al, ), and growth (Berger et al, ), the temperature thresholds identified for A. germinans leaf damage, mortality and biomass recovery can be used to help scientists and natural resource managers better anticipate mangrove range dynamics in a warming world.…”
Section: Discussionmentioning
confidence: 99%
“…In response to warming winter temperature extremes (USGCRP, ), mangroves and other tropical organisms are expected to move northward into more temperate biomes in eastern and central North America (Carter et al, ; Cavanaugh et al, ; Osland et al, ; Osland & Feher, ). In combination with temperature projections and models of mangrove propagule dispersal (Van der Stocken, Carroll, Menemenlis, Simard, & Koedam, ; Van der Stocken, Wee, et al, ), establishment (Krauss et al, ), and growth (Berger et al, ), the temperature thresholds identified for A. germinans leaf damage, mortality and biomass recovery can be used to help scientists and natural resource managers better anticipate mangrove range dynamics in a warming world.…”
Section: Discussionmentioning
confidence: 99%
“…Reported flotation and viability times for A. marina propagules are relatively short, spanning a couple of days to weeks (Clarke et al, 2001;Clarke & Myerscough, 1991;Steinke, 1986). However, it should be mentioned that the duration of the experimental trials on which these findings are based may be too short to obtain meaningful frequency distributions of these propagule traits, and should ideally extend beyond maximum values (Van der Stocken et al, 2019).…”
Section: Study Speciesmentioning
confidence: 99%
“…Estimates of gene flow and knowledge on the factors that determine the distribution of genetic diversity is not only of theoretical interest, but can be useful to inform management and conservation of these coastal ecosystems (Balbar & Metaxas, 2019;Carr et al, 2017;Nakajima et al, 2017;Pujolar et al, 2013;Schwarzbach & Ricklefs, 2001). as propagule buoyancy and viability period, species-specific propagule morphological traits (size and shape), landscape complexity, and the position of the parent tree in the tidal frame (Van der Stocken et al, 2019). Rabinowitz (1978) proposed that the interacting effects of water depth with species-specific propagule traits ("tidal sorting") might explain the differential distribution (zonation) of mangrove species along the tidal gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model appears to be common in studies of plants (Sexton et al, 2014;Segarra-Moragues et al, 2016;Cruz-Nicolás et al, 2019) and mangroves (Cerón-Souza et al, 2010;Sandoval-Castro et al, 2014;Kennedy et al, 2016;Binks et al, 2019;Ochoa-Zavala et al, 2019). Although evidence of water dispersion over long distances exists for mangrove species (Nettel & Dodd, 2007;Takayama et al, 2013;Mori et al, 2015;Van der Stocken et al, 2019b), our results indicate that the large geographic extension and major oceanic currents of the Brazilian coast physically limit the dispersal of Avicennia species. Although these correlations were significant for the total set of sampling locations, they were not significant when considering only the set of A. schaueriana and A. germinans sampling locations north of the SEC.…”
Section: Discussionmentioning
confidence: 48%